Retinoid receptor-related orphan receptor alpha: a key gene setting brain circuits - Vitalis, Tania (Neural Regen Res, 2018)
The retinoid receptor-related orphan receptor alpha (RORα) is thought to act as a constitutive activator of transcription by binding to the ROR response element (RORE) of target genes. Several mouse models in which RORα is defective have revealed the decisive roles of RORα on the development, maturation and neuroprotection of various cerebral regions including the cerebellar and somatosensory systems. We have recently shown that RORα is needed for accurate thalamic sensory system organization and somatosensory cortex development. The phenotype of various RORα deficient mice models (staggerer mutant or mouse lacking RORα in specific somatosensory regions) is, in part, reminiscent of what has been described in mice lacking thyroid hormone triiodothyronine (T3). As in in vitro studies or in other models, our studies strongly suggest that the T3/RORα-pathway, among others, is in part responsible for the staggerer phenotype. We have indeed identified some genes that were both regulated by T3 and RORα and that are known to be implicated in the cerebellar or somatosensory system development. Moreover, several groups have shown that RORα is at the crossroad of many biological processes and pathologies, including psychiatric and degenerative disorders. In particular, defective RORα-signalling has been demonstrated in humans to be associated with the emergence of autistic-like disorders. We believe that determining the appropriate amount of RORα activity could be crucial in detecting and preventing the emergence of specific brain diseases.